Effects of embryonic exposure to valproic acid on behavior and vocal development in Zebra Finch (Taeniopygia Guttata) - Soares, Annara Yve Moura (2023)
Autism Spectrum Disorder (ASD) is a condition that affects how people communicate and interact with others. These deficits may include struggle in sharing interests or emotions, failure to initiate or respond to social interactions, and difficulty with nonverbal communication, such as eye contact, facial expressions, or body language. Rodents are the most widely used animal model for studying ASD. However, since vocal communication seems to be innate in these animals, this traditional approach does not address one of the most crucial aspects of ASD, the impairment of vocal learned communication. Songbirds are among the few organisms that evolved vocal learning and related brain pathways. Vocal learning in songbirds and speech acquisition in humans share many features such as a critical period, babbling behavior, and the role of auditory and social cues for proper learning. Here, we propose a Zebra Finch, the songbird that is mostly used in laboratories, as a model to better understand autistic-like features using embryonic exposure to valproic acid (VPA), one of the environmental factors associated with ASD. Our results show that VPA exposure leads to delayed vocal development, similar to what has been observed in children with ASD. Moreover, VPA-exposed birds showed decreased social interactions, hypersensitive hearing, and altered locomotion. These results show that VPA-exposed Zebra Finch represents an attractive model to study the neurobiology of autism-related delayed vocal development.